Civil liability for damages caused by children and adolescents: problems and proposed solutions in the Peruvian legal context - Caballero Zavala, Frank Carlos (Revista de Derecho, 2024)
The article examines civil liability for damages caused by minors and adolescents in Peru, an issue that has intensified following the repeal of Article 1975 of the Civil Code by Legislative Decree 1384. The repealed article established the joint and several liabilities of parents or legal representatives. Currently, under Article 458 of the Civil Code, both minors and adolescents are civilly liable for the damages they cause, provided they act with discernment. However, the lack of patrimonial resources of minors and adolescents complicates the enforceability of reparations, leaving victims unprotected. The objectives of this study are to clarify who should bear civil liability for reparations and to explore the implications of the repeal. The methodology includes a historical and normative analysis of Peruvian legislation showing that the liability of parents and representatives has been recognized in all civil codifications since 1852. Thus, the study proposes the reintroduction of Article 1975, which would restore the joint and several liabilities of parents or representatives, thereby facilitating both the enforceability of reparations and certainty for victims.
Keywords: civil liability of children and adolescents; damage; civil compensation; joint and several liability; discernment